Audit committee adoption and firm value: Evidence from UK financial institutions - Peter Agyemang-Mintah; Hannu Schadewitz (Emerald, 2022)
Purpose: This study examines the impact of audit committee (AC) adoption on the financial value of financial institutions in the UK and also examines the impact of the establishment of an audit committee on firm value during the pre/post global financial crisis era.
Design/methodology/approach: The paper embarks on a theoretical and empirical literature review on audit committee (AC) adoption and its impact on the firm’s financial value. The paper uses data from 63 financial institutions and covers a 12-year period.
Findings: The empirical results indicate that the adoption of an AC by financial institutions has a positive and statistically significant impact on firm value. The results from the precrisis period also indicate the adoption of an AC makes a positive and significant contribution to firm value. However, there is no impact on firm value during the post-crisis period. Our results suggest that the entire UK economy experienced an economic downturn after the financial crisis (2009-2011) and financial firms were no exception.
Research limitations/implications: Our study helps to fill research gaps on the relationships between ACs and firm value as they exist in UK financial institutions. These findings are important for policy-makers and regulators.
Originality/value: To the best of our knowledge, this research is the first to conduct an empirical study of the effect of AC adoption on UK financial institutions and firm value. Second, no single study has been conducted on the effects of AC adoption and its impact on either the pre- or the post-financial crisis periods. This is the first paper to provide such empirical evidence.
Keywords: Audit committee adoption, financial institutions, UK, pre- and post-financial crisis, firm’s value.
Paper type: Empirical research.